-4n+7=10n+3

Subtract 10n from both sides of the equation.

-4n+7-10n=3

Subtract 10n from -4n.

-14n+7=3

-14n+7=3

Subtract 7 from both sides of the equation.

-14n=3-7

Subtract 7 from 3.

-14n=-4

-14n=-4

Divide each term in -14n=-4 by -14.

-14n-14=-4-14

Cancel the common factor of -14.

Cancel the common factor.

-14n-14=-4-14

Divide n by 1.

n=-4-14

n=-4-14

Cancel the common factor of -4 and -14.

Factor -2 out of -4.

n=-2(2)-14

Cancel the common factors.

Factor -2 out of -14.

n=-2⋅2-2⋅7

Cancel the common factor.

n=-2⋅2-2⋅7

Rewrite the expression.

n=27

n=27

n=27

n=27

The result can be shown in multiple forms.

Exact Form:

n=27

Decimal Form:

n=0.285714‾

Solve for n -4n+7=10n+3